Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics - Stonis, Jonas R.; Diškus, Arūnas; Vargas, Sergio A. (Zootaxa, 2019)
This is the first report of the family Tischeriidae in Colombia. We describe two new species recently discovered in the department of Valle del Cauca in southwestern Colombia: Astrotischeria ochrimaculosa Diškus, Stonis & Vargas, sp. nov., and A. colombiana Stonis & Vargas, sp. nov. The latter is a leaf miner of Asteraceae, while A. ochrimaculosa is trophically associated with Malvaceae. Astrotischeria colombiana is known only from Colombia, but A. ochrimaculosa is more widely distributed from Colombia to Peru. The new species are illustrated with photographs of their habitats, adults, male and female genitalia, and leaf mines. We comment on the rarity of tischeriids in collections and their current known distribution in the Neotropics.